(untitled) (Acta Polytechnica CTU Proceedings, 2019)
The reconstruction project deals with the unsatisfactory condition of the bridge construction, involving the railway superstructure with its signalling, communication and power equipment as well as the overhead lines all in an integrated manner. The article presents the contractor’s view of this unique project and the initial experience gained during the first year of the construction. Emphasis is laid on geological conditions and on geotechnics, especially as they relate to work on the special foundation which constitute a significant part of the reconstruction.